Cross presentation: more exotic pathwaysEpigenetic repression of MHC class I antigen presentation enables immune evasion in cancer. (October 2022) - Burr, Marian; Sparbier, Christina; Chan, Kah Lok; Lehner, Paul; Sutherland, Kate; Dawson, Mark
Abstract : Loss of MHC class I antigen presentation in cancer cells is a frequent cause of primary and acquired resistance to immunotherapy. Using a genome wide CRISPR/Cas9 screen we identify a highly conserved epigenetic repressive complex that mediates the coordinated transcriptional silencing of the MHC class I antigen processing and presentation pathway in a range of cancers, promoting immune evasion. Disruption of the complex restores tumour MHC class I antigen presentation allowing effective targeting by CD8+ T-cells. This mechanism of MHC class I repression is evolutionarily conserved and allows tumours to overcome histocompatibility barriers and grow as an allogeneic transplant in immunocompetent recipients in a mouse model of lung cancer and the transmissible Tasmanian Devil Facial Tumour 1 (DFT1). I will discuss the molecular mechanisms governing MHC-I repression both during normal development and in cancer and highlight how cancer cells co-opt an evolutionarily conserved, lineage specific function of an epigenetic complex to evade immune surveillance.